If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(-4n + -12) = 0 Reorder the terms: 9(-12 + -4n) = 0 (-12 * 9 + -4n * 9) = 0 (-108 + -36n) = 0 Solving -108 + -36n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '108' to each side of the equation. -108 + 108 + -36n = 0 + 108 Combine like terms: -108 + 108 = 0 0 + -36n = 0 + 108 -36n = 0 + 108 Combine like terms: 0 + 108 = 108 -36n = 108 Divide each side by '-36'. n = -3 Simplifying n = -3
| 7x+.1+10x-.2=5 | | 3x+y=6forx | | x^4+x^3=4x^2+4x | | -5(-5w+1)= | | 10-6w=-10 | | 3x-(2x+6)=2x-24 | | 8h=40 | | 2(-7v-8)=-86 | | 8B=-5+8B | | 2j=56 | | 25x+-45=180 | | 2(-2c-9)= | | 43=k-14 | | 3+2=-7 | | 7(5k+2)= | | 525+0.21d=585+0.13d | | 8x+3+4x=90 | | X^2-8x+12=24 | | -8(4m-9)= | | y^2=20-x^2 | | 8g-6g=8 | | 2x+1-x=-12 | | -w+173=3 | | 246=193-v | | 233-u=127 | | 49x^8+42x^4+9=f(x) | | 36-3w=w | | 7(6k-4)+3k=-388 | | 4x=5(3) | | 14x-16=124 | | 6v=4v+16 | | solvem-3.41=10.7 |